2014
DOI: 10.1002/ange.201407807
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible and Selective Inhibitor of Monoacylglycerol Lipase Ameliorates Multiple Sclerosis

Abstract: Monoacylglycerol lipase (MAGL) is the enzyme responsible for the inactivation of the endocannabinoid 2arachidonoylglycerol (2-AG). MAGL inhibitors show analgesic and tissue-protecting effects in several disease models. However, the few efficient and selective MAGL inhibitors described to date block the enzyme irreversibly, and this can lead to pharmacological tolerance. Hence, additional classes of MAGL inhibitors are needed to validate this enzyme as a therapeutic target. Here we report a potent, selective, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 35 publications
0
35
0
2
Order By: Relevance
“…Sham or TMEV infected mice were treated daily for seven consecutive days (0–7 dpi) with 2‐AG (5 mg/kg; i.p. ), the reversible inhibitor of 2‐AG degradation UCM‐03025 at a dose of 5 mg/kg that increases CNS levels of 2‐AG on the basis of previous studies (Hernández‐Torres et al, ; Feliú et al, ), or vehicle alone (10% ethanol or 10% DMSO + phosphate buffer saline [PBS], respectively). In the studies at day 1 post‐infection, mice were treated at day 1 and 0 before infection with 2‐AG (5 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sham or TMEV infected mice were treated daily for seven consecutive days (0–7 dpi) with 2‐AG (5 mg/kg; i.p. ), the reversible inhibitor of 2‐AG degradation UCM‐03025 at a dose of 5 mg/kg that increases CNS levels of 2‐AG on the basis of previous studies (Hernández‐Torres et al, ; Feliú et al, ), or vehicle alone (10% ethanol or 10% DMSO + phosphate buffer saline [PBS], respectively). In the studies at day 1 post‐infection, mice were treated at day 1 and 0 before infection with 2‐AG (5 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Here, we address whether the exogenous administration of 2‐AG, or the elevation of endogenous 2‐AG tone by inhibiting its degradation with the compound UCM‐03025 that inhibits MAGL with high potency (IC 50 = 180 nM) and selectivity vs FAAH (IC 50 = 59 μM), ABDH‐6 and ABDH12 (no inhibition at 10 μM; Hernández‐Torres et al, ), affects the immune response to TMEV. Intracraneal infection with TMEV induced CNS inflammation that was evident at day 7 post‐infection (dpi) involving the participation of both microglial cells and immune infiltrates (Mecha, Carrillo‐Salinas, Mestre, Feliú, & Guaza, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in CSPG expression by MAGL inhibitors and by 2‐AG in cultured astrocytes is consistent with our previous data obtained in vivo, whereby administration of the same MAGL inhibitor (UCM03025) reduced astrogliosis and CSPG accumulation in the spinal cord of a chronic progressive mouse model of MS (Feliu et al, ). Indeed, 2‐AG and other MAGL inhibitors were previously shown to attenuate symptoms in the EAE model (Bernal‐Chico et al, ; Hernández‐Torres et al, ; Lourbopoulos et al, ). It is important to remark that in the present study MAGL is the hydrolysis enzyme that plays the main role in regulating the availability of 2‐AG to reduce neurocan (in agreement with MAGL high expression in astrocytes), whereas ABDH6 may play a secondary role that in conjunction with MAGL is also crucial for the reduction of neurocan.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the endocannabinoid 2‐arachidonoylglycerol (2‐AG) promotes the proliferation and differentiation of OPCs (Gómez et al, , , ) and it regulates their migration in culture (Sánchez‐Rodríguez, Gómez, Esteban, García‐Ovejero, & Molina‐Holgado, ). Actually, in vivo studies also demonstrated that inhibiting 2‐AG catabolism through the inhibition of monoacylglycerol lipase (MAGL) or the direct administration of 2‐AG attenuates symptomatology and promotes remyelination in the autoimmune EAE model (Bernal‐Chico et al, ; Hernández‐Torres et al, ; Lourbopoulos et al, ), as well as in the Theiler virus model of MS (Feliu et al, ; Mecha et al, ). The effects of 2‐AG on disease activity and remyelination in the latter progressive model of MS are dependent on the CB1 and CB2 cannabinoid receptors (CB1R and CB2R), and they involve immune modulation in conjunction with a reduction in astrogliosis and CSPG deposition (Feliu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Her report on a monoacylglycerol lipase inhibitor was featured on a cover of Angewandte Chemie. [6] Enrique Ortí (Universitat de Valncia; UV) studied at the UV, where he completed his PhD (in 1985) under the supervision of Francisco Tomµs and JosØ Sµnchez. After a postdoctoral stay with Jean-Luc BrØdas at the UniversitØ de Namur, he returned to the UV, where he was made full professor in 2008.…”
mentioning
confidence: 99%